Community Empowerment of Tanjung Benoa Village Bali Through Collaborative Workshop of Kamala Madya Dance - Ruspawati, Ida Ayu Wimba; Widyastuti, Ida Ayu Gede Sasrani (Jayapangus Press, 2025)
The background of this study lies in the partner's need for additional dance materials to diversify tourist performances and enrich the artistic offerings of their community-run studio. The objective is to analyze the collaborative process between the choreographer (researcher) and the local art studio, Sanggar Sekar Segara Madu, in developing an original dance performance. This research aims to empower the art community in Tanjung Benoa Village through the collaborative creation of the Kamala Madya dance. A qualitative method was employed, using reflective narrative techniques and in-depth interviews with dancers and facilitators to gather data. The results show that the collaboration successfully produced the Kamala Madya dance, which is artistically valuable and culturally grounded in Hindu philosophical principles. The choreographer and composer translated creative concepts into choreography and music, while the partners contributed by designing costumes and mobilizing local dancer talent. This collaborative effort has positively impacted the local community by fostering cultural expression, strengthening local identity, and enhancing the studio’s repertoire. In conclusion, this study demonstrates how participatory choreography can be a powerful tool for community empowerment, with implications for sustaining local cultural industries and encouraging further research into collaborative arts practices and their role in preserving cultural heritage.